2011
DOI: 10.2478/v10035-011-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Surgical Management and Early Postoperative Outcome in a Cohort of Gastric Cancer Patients of a Tertiary Referral Center in Relation to Multi-Center Quality Assurance Studies

Abstract: the aim of the study was to analyze epidemiologic parameters, treatment-related data and prognostic factors in the management of gastric cancer patients of a university surgical center under conditions of routine clinical care before the onset of the era of multimodal therapies. By analyzing our data in relation with multi-center quality assurance trials [German Gastric Cancer Study -GGCS (1992) and East German Gastric Cancer Study -EGGCS (2004)] we aimed at providing an instrument of internal quality control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In other organs, including the skin, taste buds, and lungs, Lgr6 has been identified as a stem cell marker (Snippert et al, 2010 ; Oeztuerk-Winder et al, 2012 ; Ren et al, 2014 ), and these Lgr6-positive stem cells have been reported to be involved in wound repair and hair follicle development (Barker and Clevers, 2010 ; Snippert et al, 2010 ; Leushacke and Barker, 2012 ). Lgr6 expression is sometimes up-regulated in gastric cancer, and Lgr6 expression is significantly correlated with patient survival; patients with Lgr6-positive tumors tend to live longer than patients with Lgr6-negative tumors (Krejs, 2010 ; Garlipp et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In other organs, including the skin, taste buds, and lungs, Lgr6 has been identified as a stem cell marker (Snippert et al, 2010 ; Oeztuerk-Winder et al, 2012 ; Ren et al, 2014 ), and these Lgr6-positive stem cells have been reported to be involved in wound repair and hair follicle development (Barker and Clevers, 2010 ; Snippert et al, 2010 ; Leushacke and Barker, 2012 ). Lgr6 expression is sometimes up-regulated in gastric cancer, and Lgr6 expression is significantly correlated with patient survival; patients with Lgr6-positive tumors tend to live longer than patients with Lgr6-negative tumors (Krejs, 2010 ; Garlipp et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, accurate preoperative determination of the GC stage is essential in the selection of an appropriate therapeutic mode. Previously, precise preoperative staging was not essential because the exact stage did not alter treatment plans (Garlipp et al, 2011). Endoscopic ultrasonography (EUS), which is considered to be the method of choice for locoregional staging, was commonly used for the differentiation of mucosal from submucosal lesions (Ganpathi et al, 2006;Jurgensen et al, 2013;Karimi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%